Effect of the synthetic coumarin, ethyl 2-oxo-2H-chromene-3-carboxylate, on activity of Crotalus durissus ruruima sPLA2 as well as on edema and platelet aggregation induced by this factor - Fonseca, F. V. [UNESP]; Baldissera, L.; Camargo, E. A. de [UNESP]; Antunes, E.; Diz-Filho, E. B. S. [UNESP]; Correa, A. G.; Beriam, L. O. S.; Toyama, D. O.; Cotrim, C. A. [UNESP]; Toyama, M. H. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
We show that ethyl 2-oxo-2H-chromene-3-carboxylate (EOCC), a synthetic coumarin, irreversibly inhibits phospholipase A(2) (sPLA2) from Crotalus durissus ruruima venom (sPLA2r) with an IC(50) of 3.1 +/- 0.06 nmol. EOCC strongly decreased the V(max) and K(m), and it virtually abolished the enzyme activity of sPLA2r as well as sPLA2s from other sources. The edema induced by 5PLA2r + EOCC was less than that induced by 5PLA2r treated with p-bromophenacyl bromide, which was more efficient at neutralizing the platelet aggregation activity of native 5PLA2r. Native 5PLA2r induced platelet aggregation of 91.54 +/- 9.3%, and sPLA2r +/- EOCC induced a platelet aggregation of 18.56 +/- 6.5%. EOCC treatment also decreased the myotoxic effect of sPLA2r. Mass spectrometry showed that EOCC formed a stable complex with sPLA2r, which increased the mass of native 5PLA2r from 14,299.34 da to 14,736.22 Da. Moreover, the formation of this complex appeared to be involved in the loss of 5PLA2r activity. Our results strongly suggest that EOCC can be used as a pharmacological agent against the 5PLA2 in Crotalus durissus sp. venom as well as other sPLA2s. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Crotalus durissus ruruima; Edema; Myonecrosis; Platelet; sPLA2; Synthetic coumarin